Experimental Quantum Cryptography based on the BB84 Protocol - Deachapunya, S.; Chiangga, S.; Weinfurter, H. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Quantum cryptography is a new technique that provides verifiable secure key exchange between the sender and the receiver. The security of the quantum cryptographic system is protected by the laws of quantum physics, which ensure that any eavesdropping can always be detected. This is in strong contrast with classical key exchange, where the security depends on (unprovable) assumptions. Recent experimental implementation of quantum cryptography achieved about 50 km point-to-point key exchange over optical fibers and about 1 km over a free space connection in daylight. Here we report the development of experimental free space quantum cryptographic systems based on the BB84 protocol. Our system does not use any active manipulation elements, resulting in compactness, reliability and easy handling. Keywords: quantum cryptography, quantum information Corresponding author: E-mail: cast@kmitl.ac.th